THE CENTER CONDITIONS FOR A CLASS OF CUBIC SYSTEMS - Dolichanin, Ć.; Romanovsky, V. G.; Stefanović, M. (Matematichki Bilten, 1996)
One of famous problems of the theory of Differential equations, namely, center-focus problem, are considered. For the cubic vector field\[i\frac{dw}{dt}=w\left(1-a_{10}w-a_{01}\overline{w}-a_{11}w\overline{w}-a_{-13}w^{-1}\overline{w}^{3}\right),\]in the case when \(a_{11} e -a_{10}a_{01}\) the necessary and some sufficient center conditions are obtained.